Sarawak local dialect (Sarawak Malay) translator / Ophelia Mawas Isa - Isa, Ophelia Mawas (2017)
The emergence of mobile application has brought along new possibilities to all walks of life in various communities. There are many mobile translator application created for most of the major languages in the world and not many of them is available for the less used language such as Sarawak Malay dialect. There are several problems encountered for example Sarawak Malay is not as practical as other languages that have been spoken in Malaysia. For instance, the pronunciations for Sarawak local dialect are different from other dialect and the language barriers. Apart from that, the objectives of this application are to identify requirements, design and develop the Sarawak Local Dialect (Sarawak Malay) Translator. Moreover, the development of Sarawak Local Dialect (Sarawak Malay) Translator is significance towards tourism in Sarawak. It is to minimize the language barriers between the native speaker and the tourist. Besides, it can be a jumpstart towards the ecotourism of Sarawak moreover to promote more about Sarawak to other country. As for the outcome, users are able to use this application to communicate with the local without wrangled around and this application is an offline-based. Mobile Application Development Life Cycle was chosen as a methodology for development of this mobile application. The mobile application usage is spreading periodically. Each mobile application is outlined using the best development procedure. In a nutshell, this Sarawak Local Dialect (Sarawak Malay) Translator is an application that provides a mini dictionary where it can help tourist that come to Sarawak.